Efeito da radiação UV -B na interação Botrytis cinerea – clonostachys rosea em morangueiro e do ácido 4 - aminobenzóico no controle do patógeno em tabaco - Costa, Lúcio Bertoldo [UNESP] (2014)
The incidence of ultraviolet (UV 100 to 400 nm) in the earth , especially UV - B radiation (280 - 320 nm) is being altered with climate change. The solar radiation is an import ant component for the development of microorganism in the environment, thus is important evaluate the tolerance of plant pathogens as well as the biocontrol agents to UV - B radiation. T he present study aimed to study the interaction of strawberry x Botrytis cinerea x Clonostachys rosea x UV - B radiation. There were significantly differences among the thirteen B. cinerea strains in relation to spore germination and sporulation on leaf disks after irradiation ranging from 2.9 to 8.9 KJ m - 2 . The relative germina tion ranged from 95 to 75% and the sporulation varied more than 100% among B. cinerea strains after exposure to 4 radiation of 6.4 KJ m - 2 . The LQC - 150 strain showed high germination and sporulation on leaf disk after irradiation and was selected as a toleran t strain. Survival curve of B. cinerea strain LQC - 150 showed lethal dose 50 (LD 50 ) of 6.2 KJ m - 2 . The sporulation of both fungi on leaf disks was inversely proportional to the dose of UV - B radiation, while inoculated alone. When confronted in the same leaf disk and not irradiated, C. rosea reduced the incidence of the pathogen and its sporulation in about 50% and 80%, respectively. However, the ability of C. rosea to control B. cinerea on leaf disks was gradually reduced with the increase of UV - B radiation, reaching 20% and 50%, respectively for pathogen incidence and sporulation, on higher UV - B doses. When the bioagent was applied in the morning, the development was lower than when applied afternoon. The effect of PABA in the induction of resistante in plan ts of Nicotiana benthamiana against B. cinerea was evaluated and it was found that plants treated with PABA were more resistant to the pathogen. The evaluations of size of plants and leaves ...